Dynamic Changes at Yahtse Glacier, the Most Rapidly Advancing Tidewater Glacier in Alaska - Durkin, William J.; Bartholomaus, Timothy C.; Willis, Michael J.; Pritchard, Matthew E. (Frontiers in Earth Science, 2017)
Since 1990, Yahtse Glacier in southern Alaska has advanced at an average rate of ~100 m year−1 despite a negative mass balance, widespread thinning in its accumulation area, and a low accumulation-area ratio. To better understand the interannual and seasonal changes at Yahtse and the processes driving these changes, we construct velocity and ice surface elevation time series spanning the years 1985–2016 and 2000–2014, respectively, using satellite optical and synthetic aperture radar (SAR) observations. We find contrasting seasonal dynamics above and below a steep (up to 35% slope) icefall located approximately 6 km from the terminus. Above the icefall, velocities peak in May and reach their minima in October synchronous with the development of a small embayment at the calving terminus. The up-glacier minimum speeds, embayment, and plume of turbid water that emerges from the embayment are consistent with an efficient, channelized subglacial drainage system that lowers basal water pressures and leads to focused submarine melt in the calving embayment. However, velocities near the terminus are fastest in the winter, following terminus retreat, possibly off of a terminal moraine that results in decreased backstress. Between 1996 and 2016 the terminus decelerated by ~40% at an average rate of ~0.4 m day−1 year−1, transitioned from tensile to compressive longitudinal strain rates, and dynamically thickened at rates of 1-6 m year−1, which we hypothesize is in response to the development and advance of a terminal moraine. The described interannual changes decay significantly upstream of the icefall, indicating that the icefall may inhibit the upstream transmission of stress perturbations. We suggest that diminished stress transmission across the icefall could allow moraine-enabled terminus advance despite mass loss in Yahtse's upper basin. Our work highlights the importance of glacier geometry in controlling tidewater glacier re-advance, particularly in a climate favoring increasing equilibrium line altitudes.